Correlates of Index Futures and Spot Index Volatility: A Study of Indian Stock Market - Ganai, Dr. Khurshid Ali (Archives of Business Research, 2019)
In this paper an analysis on the dynamic relationship between Index Futures and Spot Index Volatility is carried out to ascertain the extent of influence that Index Futures hold over underlying (spot index). For this purpose relevant intraday data from 1st April 1998 – 31st March 2000 of S&P CNX NIFTY (50) are used to measure the level of volatility of spot Index during the pre-derivatives period. The second reference period is taken from 1st 0ctober 2000 – 30th September 2002 to determine the level of volatility during the post-derivatives period. This is followed by a comparative analysis of both the periods and the findings put forth by the comparison affirms that there exists a significant correlation between index futures and underlying volatility (Spot Index) as the level of the volatility throughout the post-derivatives period has had a considerable decline. The findings of this study collaborate and strengthen the results of many studies mentioned in the review.